Reaccionarios, traidores y otras malas hierbas políticas.La representación visual del antirrepublicanismo en El Motín (1881-1895) - Lara Campos Pérez (Cahiers de Civilisation Espagnole Contemporaine, 2023)
This article studies the image of the anti-republican «other», developed and spread by El Motín, one of the most important satirical republican newspapers during the period known in Spain as «La Restauración». To this end, it analyses a selection of the illustrations published in this newspaper about this theme, regarding the characters the narrative sequence present in them, as well as the visual rhetoric resources used by the successive cartoonists who produced them. The aim is to elucidate the extent to which this image of the anti-republican «other» served as a binding force for the definition of a republican «we», at a time of great fragmentation within Spanish republicanism.